Study of calcium/lead apatite structure type for stabilising heavy metals - Dong, Zhili (2011)
(CaxPb10-x)(VO4)6F2 apatites were synthesised and their microstructures were studied using powder X-ray diffraction, scanning electron microscopy and transmission electron microscopy before and after leach testing. X-ray diffraction showed that the apatites were hexagonal with a ≈ 10Å and c ≈ 7Å. During the leach test, Pb was released into the solution more slowly than Ca, which is desirable as the immobilisation of Pb is of importance. The experimental results also showed that V was almost undetectable in the leaching test solutions. In the (Ca7Pb3)(VO4)6F2 pellet, Ca and Pb distributions were not homogenous from one grain to another. Microstructural evidence from scanning electron microscopy revealed that the dissolution via development of etch pits began at grain boundaries and inside grains, and progressed faster in Ca rich regions. These results suggest that apatites of high Pb to Ca ratio are more durable.